The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1016/j.iimb.2010.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Work–family balance of Indian women software professionals: A qualitative study

Abstract: One of the significant changes witnessed in the labour markets in India has been the entry of women IT professionals in the rapidly growing software services sector. As the women take on the role of working professional in addition to their traditional role of the homemaker, they are under great pressure to balance their work and personal lives. This study attempts to understand how work and family related factors influence the workefamily balance of Indian women IT professionals. The study is based on an expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
103
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(114 citation statements)
references
References 46 publications
10
103
0
1
Order By: Relevance
“…Ocak /January 2014 -Cilt/Vol: 16 -Sayı/Num: 01 caused the increase women's organizational commitment and their contribution to the economy (Valk and Srinivason, 2011). Schueller and Alexandra (2012) state that after women have joined in the work life, they have had imbalance between their careers and housewife roles and they have problems about their leadership position.…”
Section: "İş Güç" Endüstri İlişkileri Ve İnsan Kaynakları Dergisi "Imentioning
confidence: 99%
“…Ocak /January 2014 -Cilt/Vol: 16 -Sayı/Num: 01 caused the increase women's organizational commitment and their contribution to the economy (Valk and Srinivason, 2011). Schueller and Alexandra (2012) state that after women have joined in the work life, they have had imbalance between their careers and housewife roles and they have problems about their leadership position.…”
Section: "İş Güç" Endüstri İlişkileri Ve İnsan Kaynakları Dergisi "Imentioning
confidence: 99%
“…Some wives were uncomfortable with and experienced some conflict about husbands' changed role in the home as they felt they had negated the cultural norm of being 'good' mothers and wives. However, younger wives did not experience any discomfort about husbands assisting with housework and childcare (Valk & Srinivasan, 2011), which indicated that society was changing and there was a shift away from upholding traditional norms in the home. However, the cultural identity negotiation of some male participants did not take place immediately.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, it also means better human resource policies for developing and optimizing talent pools due to better understanding on the roles played by IT professionals (Valk & Srinivasan, 2011). The implications could be mirrored in better overtime payments or shift rotating to reduce work family conflict as well.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…In the Information Technology (IT) industry, it has been reported that the entries of female IT professionals in the rapidly developing software service sector have induced profound changes to the labor market in India (Valk & Srinivasan, 2011). This has motivated Valk and Srinivasan (2011) to examine the effect of work and family related factors on WLB of Indian female IT professionals to encourage and ensure continued growth of women participation in the industry.…”
Section: Introductionmentioning
confidence: 99%